Community Empowerment through Waste Management into Ecobricks - Ardan, Ghilmanul; Putri, Inge Wiliandani Setya; Wardoyo, Arik Aguk; Perdani, Zahrotul Putty; Zahro, Vikka Fatimatus; Maulana, Mohammad Sheidqi (Edujavare Publishing, 2024)
Plastic waste in eco-bricks is one of the innovative solutions to reduce the negative impact of plastic waste on the environment. Ecobricks are plastic bottles filled densely with non-organic plastic waste cut into small pieces, forming a sturdy building material that can be used for various construction purposes. The socialization program for the use of waste in eco-bricks is one of the important initiatives in overcoming the increasingly worrying problem of plastic waste. This program aims to increase public awareness about the importance of plastic waste management, reduce the amount of plastic waste that ends up in landfills, and provide alternatives to using plastic waste that is more useful. This service uses the PAR (Participatory Action Research) method by directly providing education to students, including the lecture and question and answer method. Through this socialization, the community is invited to actively participate in making eco-bricks, understand the techniques and benefits, and apply them in daily life. The result of this service is creating a cleaner environment, reducing plastic pollution, and forming collective awareness to preserve the environment through concrete actions. This service concludes that eco-bricks are an effective and sustainable solution to overcome the problem of plastic waste while providing added value to the community. Further development and socialization of the use of eco-bricks are expected to encourage wider participation from the community in managing plastic waste creatively and environmentally friendly.